Corporate Dividend Policies: Lessons from Private Firms - Michaely, Roni; Roberts, Michael R. (Review of Financial Studies, 2012)
[We compare the dividend policies of publicly and privately held firms in order to help identify the forces shaping corporate dividends, and shed light on the behavior of privately held companies. We show that private firms smooth dividends significantly less than their public counterparts, suggesting that the scrutiny of public capital markets plays a central role in the propensity of firms to smooth dividends over time. Public firms pay relatively higher dividends that tend to be more sensitive to changes in investment opportunities than otherwise similar private firms. Ultimately, ownership structure and incentives play key roles in shaping dividend policies.]